Demystifying the evaluation of brands endorsed by religious leaders in the emerging markets - Arli, Denni; Gupta, Narain; Sardana, Deepak; Sharma, Piyush (Emerald, 2022)
Purpose: This paper uses social identity theory to investigate the sequential mediating effects of extrinsic religiosity and perceived role of religious leaders in the impact of consumers' intrinsic religiosity on perceived value of brands endorsed by religious leaders.